Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Daya Beli Pada PT. Sidosemi Berkah Abadi - Muhammad Nur Aziz; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine and analyze the effect of product quality, price and promotion on purchasing power at PT. Sidosemi Berkah Abadi. The population in this study is the people of Malang City who have ordered catering PT. Sidosemi Berkah Abadi. in the last four months, March 2022-July 2022. The data collection method in this study used a questionnaire with a sample of 65 respondents. The independent variable in this study is the effect of Product Quality, Price and Promotion. While the dependent variable is Purchasing Power. The analytical method used in this study is multiple linear regression analysis and processed using SPSS version 22. The results of this study show that product quality, price and promotion have a significant positive effect simultaneously on purchasing power. Partially Product Quality and Promotion have a positive and significant effect on purchasing power. The price has a negative effect on purchasing power. Keywords: Product Quality, Price, Promotion, Purchasing Power.